IMPROVING METHODS OF ECONOMIC ANALYSIS OF HOUSEHOLD APPLIANCES IMPORTED BY INDIVIDUALS THROUGH CUSTOMS - Muydinova , Zilola (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This study explores the improvement of economic analysis methods for household appliances imported by individuals through customs. The growing volume of these imports influences domestic markets, consumer demand, and fiscal policy. The research identifies weaknesses in traditional analytical approaches and proposes digitalized, data-driven, and econometric methods to enhance the efficiency and accuracy of customs economic analysis. The findings suggest that integrating real-time customs data and predictive modeling tools can significantly improve trade monitoring and policy development.